Development of air drying methods for paperboard - Tung, Jian Seng (2022)
Paperboard is a popular material that has been widely used as food packages, shirt boards and shoe midsole boards. In the current paperboard industry, an air drying method is adopted by drying the paperboard in an open-shed dryer. The solar energy has been widely applied in drying foods and crops. However, there is no review work was entirely contributed to the use of solar dryers in pulp and paper industry. Besides, drying paperboard in a high humidity and low temperature region through open-shed dryer could cause inefficient drying and the growth of microorganism such as fungus. The aim of this study is to develop an air-drying method which could improve the current drying process of paperboard. The study focused on the factors that affect the drying rate including the air flow, temperature and relative humidity (RH). Greenhouse solar dryer (GHSD) was introduced in this study to compare the drying performance with open-shed dryer. In this study, three-dimensional computational fluid dynamics (CFD) simulations were implemented to analyse the drying environment in the open-shed dryer and GHSD models with different openings configurations in a site having an ambient condition of 31 °C and 80% RH. From the results, it was found that the GHSDs have better drying performance than open-shed dryer with the controlled air flow, 6.7 to 32.6 °C higher temperature and 19.6 to 55.7 % lower RH. Besides, it was found that the drying environment in the GHSDs were strongly related to the openings configurations. A large opening area could results in high ventilation rate through the dryer which causes lower drying temperature due to the poor heat retention. Based on the results, an optimized design of GHSD was proposed with the idea of achieving a compromise between the ventilation and heat retention performance by implementing mechanical ventilation with natural ventilation. An exhaust fan was applied in the GHSD and the configuration of opening was modified. The proposed GHSD with optimized design has a better drying performance than the open-shed dryer by achieving 11.2 ℃ higher temperature and 29.8 % lower RH which led to an improvement of drying rate by 52.4 %. Also, it was recommended that the paperboard samples are oriented in parallel to the inflow of air during the drying process to ensure an uniform drying in the dryer.